Efeito de proteases isoladas da fração LPII do látex de calotropis procera na prevenção da mucosite intestinal induzida por irinotecano em camundongos - Rangel, Gisele de Fátima Pinheiro (2019)
Intestinal mucositis (IM) is a common side effect of irinotecan (CPT-11), is chemotherapeutic used for the treatment of metastatic colorectal cancer. About 80% of irinotecan-treated patients develop some degree of MI. Calotropis procera is a latiferous plant that has an anti-inflammatory potential in several models. Objective: To investigate the pharmacological potential of an isolated fraction of Calotropis latex (LPII), on the morphological changes, inflammation and forms associated with intestinal mucositis induced by irinotecan in mice. Methods: Swiss male mice (25-30 g) received irinotecan (75 mg / kg, i.p.) or saline (0.9%, i.p.) once daily for four days. In other experimental groups, LPII (5 mg / kg; i.v) and LPII plus protease inhibitor (IAA), LPII + IAA (1, 5 or 25 mg / kg, i.v) were injected one hour earlier. The animals were euthanized in the experimental protocol, and peripheral blood samples were collected for leukocyte counts and duodenum for analysis of intestinal contractility, histopathological changes, and MPO, GSH, MDA, cytokines (IL-1β, IL-6, KC and IL-10), expression of COX-2 and NF-κB. Diarrhea scores and changes in the length of the small intestine were also evaluated. In addition, the animals were heavily criticized for body mass and survival. Statistical analysis ANOVA / Bonferroni test or Kruskal Wallis / Dunn test was used. p <0.05 was accepted. Results: The protein fraction of LPII did not alter the relative parameters, such as diarrhea, intestinal length and survival, although it reduced the MPO concentration, demonstrating its anti-inflammatory activity. Influence of LPII IAA to inhibition growth, inhibition of proteolytic activity, increased survival and intestinal function, increased survival, reduced concentration of inflammatory cytokines (IL-1β, IL-6, KC) COX-2 and NF-Kb, increased an anti-inflammatory protein (IL-10), associated with antioxidants, demonstrated by the increase of GSH concentration and reduction of MDA. Conclusion: The effect of proteins isolated from C.procera latex on IM by CPT-11 is the protease protein, however, a proteolytic activity of proteins appears to be modulating the negative form of its pharmacological effect.